2013
DOI: 10.1007/s00216-013-7225-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical flow field-flow fractionation as a novel technique for the analysis of PS-b-PI copolymers

Abstract: Asymmetrical flow field-flow fractionation (AF4) was used as a fractionation technique to investigate the molecular heterogeneity of poly(styrene-b-isoprene) diblock copolymers synthesized by either sequential living anionic polymerization or coupling of living precursor blocks. AF4 coupled to multi-angle laser light scattering (MALLS), refractive index (RI), and ultraviolet (UV) detectors was used to separate the diblock copolymers from the homopolymers and coupling products, and the molar masses of the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[ 7 ] ThFFF can thus fractionate analytes according to size ( D ) as well as chemical composition ( D T ) and, as a consequence, has been applied to the characterization of a variety of polymers. [ 8,9 ] The capabilities of ThFFF in separating polymers according to tacticity and microstructure have been discussed recently. [ 2,3 ] The infl uence of solvent composition on polymer retention behavior has been extensively studied and it was demonstrated that solvent composition, as well as viscosity, can have a signifi cant infl uence.…”
Section: Fractionation Of Poly(butyl Methacrylate) By Molecular Topol...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] ThFFF can thus fractionate analytes according to size ( D ) as well as chemical composition ( D T ) and, as a consequence, has been applied to the characterization of a variety of polymers. [ 8,9 ] The capabilities of ThFFF in separating polymers according to tacticity and microstructure have been discussed recently. [ 2,3 ] The infl uence of solvent composition on polymer retention behavior has been extensively studied and it was demonstrated that solvent composition, as well as viscosity, can have a signifi cant infl uence.…”
Section: Fractionation Of Poly(butyl Methacrylate) By Molecular Topol...mentioning
confidence: 99%
“…Furthermore, D is dependent on the size of the analyte in solution, whereas D T is dependent on the chemical nature of the analyte and the solvent . ThFFF can thus fractionate analytes according to size ( D ) as well as chemical composition ( D T ) and, as a consequence, has been applied to the characterization of a variety of polymers …”
Section: Introductionmentioning
confidence: 99%
“…molecular weight and polydispersity) of the BCP. 28,29,42,43 In this work, we present the application of BCP chromatographic fractionation to create tailored inorganic mesoporous thin films. Crucially, we identify the role of molecular weight, composition and dispersity on the resulting pore size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…molecular weight and polydispersity) of the BCP. [40][41][42][43] In this work, we present the application of BCP chromatographic fractionation to create tailored inorganic mesoporous thin films. Crucially, we identify the role of molecular weight, composition and dispersity on the resulting pore size distribution.…”
Section: Introductionmentioning
confidence: 99%